Laparoscopic Ladd’s procedure for intestinal malrotation in small infants with midterm follow-up - Xuepeng Zhang; Lvna Xiang; Tong Qiu; Jiangyuan Zhou; Guowei Che; Yi Ji; Zhicheng Xu (BMC Gastroenterology, 2023)
Abstract Background The objective of this study was to evaluate the safety and efficacy of laparoscopic Ladd’s procedure (LL) for intestinal malrotation (IM) in small infants. Methods All patients aged < 6 months with IM who underwent Ladd’s procedures between January 2012 and December 2019 were enrolled. The perioperative demographics and midterm follow-up results were retrospectively reviewed and compared between patients who underwent LL and open Ladd’s operation (OL). Results Fifty-five patients were enrolled for analysis. The baseline characteristics were well matched in the two groups. The rate of volvulus was similar in the two groups (76.2% vs. 73.5%, P = 0.81). Two cases in the LL group were converted to OL due to intraoperative bleeding and intestinal swelling. The operative time (ORT) was not significantly different between the two groups (73.8 ± 18.7 vs. 66.8 ± 11.6 min, P = 0.76). Compared to the OL group, the LL group had a shorter time full feed (TFF) (3.1 ± 1.2 vs. 7.3 ± 1.9 days, P = 0.03) and a shorter postoperative hospital stay (PHS) than the OL group (5.5 ± 1.6 vs. 11.3 ± 2.7 days, P = 0.02). The rate of postoperative complications was similar in the two groups (9.5% vs. 11.8%, P = 0.47). The LL group had a lower rate of adhesive obstruction than the OL group, but the difference was not significant (0.0% vs. 11.8%, P = 0.09). One patient suffered recurrence in the LL group, while 0 patients suffered recurrence in the OL group (4.8% vs. 0.0%, P = 0.07). The rate of reoperation in the two groups was similar (4.8% vs. 8.8%). Conclusions The LL procedure for IM in small infants was a safe and reliable method that had a satisfactory cosmetic appearance and shorter TFF and PHS than OL.